The impact of perceived export barriers on export performance : a case study of Ghanaian non-traditional firms - Kennedy, Doragia; Nicholas, Adu-Gyamfi (Høgskolen i Bodø, 2009)
Mastergradsoppgave i bedriftsøkonomi - Høgskolen i Bodø, 2009 Over the years there have been substantive studies albeit contradictory findings on the relationship between perceived export barriers and export performance (Madsen, 1987; Zou and Stan, 1998; Aaby and Slater, 1989), on firms of different sizes and resources across a wide variety of industries. In spite of the increasing research on export performance in business studies, the major focus has mainly been on studies within the scope of western market context. There have been relatively few studies done with respect to this in a developing market context such as sub-Saharan Africa and particularly Ghana. This literary gap has been the main motivation for this thesis. We reviewed prior literature and conducted a survey of 100 Ghanaian non-traditional export firms. Our findings supported our main hypothesis that there is a negative relationship between perceived export barriers and export performance. Other findings support the hypothesis that internal management forces and firm size had a negative relationship with perceived export barriers. However, two of our hypotheses that firm internationalization had a negative relationship with perceived export barriers and that firm commitment had a positive relationship with export performance were not support Findings from this study adds up to prior literature by isolating for discussion variables which contribute to the improvement of both perceived export barriers and export performance measures in a sub-Saharan African country context. Some of the noted limitations during our study include the following; first, scanty research work on problems pertaining to exporting firms from developing countries served as a major limitation of our work. The lack of research on the subject with particular reference to developing country context indicates the lack of theories and methodologies developed specifically for the context of a sub-Saharan African country. Findings from this study can be adapted to serve as a ...